Application of Queue Theory in Campus Transportation at Padjadjaran Jatinangor University Using a Multiserver Queue System Model - Aufhar, Ihkam Amalul; Sudradjat; Nahar, Julita (iora, 2025)
Trasnportation system on campus is an important aspect that supports the mobility of the Academic Community and the relations or partners of Padjadjaran University. Currently, Padjadjaran Jatinangor University provides several public transportation facilities that can be used around campus area, namely conventional motorcycle taxis, Beam electric bicycles, and campus transportation in the form of buses. Based on the results of a survey conducted by the author, campus transportation is a facility of public transportation that is more often used and in demand by the Academic Community compared to the other two facilities of public transportation. This study aims to analyze the performance of the passenger queuing system on that campus transportation using a multiserver queue system model. Data in the arrival rate of bus passenger ( ) and the rate of bus service ( ) were collected through direct observation. The results of the study showed that during the operating hours at 07:00-08:00, routes A, B, and C are optimal with number of buses as many as 5, 5, and 6 respectively. Then, during operating hours at 09:45-10:45, routes B and C are optimal with number of buses each as many as 3 buses. As for route A, it is necessary to reduce the number of buses by 1 piece. Then during operating hours at 13:00-14:00, all routes need to be reduced to 1 bus each.